Strategi Active Learning Berbasis Jigsaw dalam Meningkatkan Keaktifan Belajar Siswa pada Pembelajaran Pendidikan Agama Islam di SMP Negeri 18 Kota Jambi - Rahmawati; Nasir (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
The increasing demand for student-centered and dialogical learning in twenty-first-century education has intensified the need for innovative pedagogical approaches capable of fostering meaningful student engagement within religious education classrooms. However, Islamic Religious Education learning in many secondary schools remains predominantly teacher-centered, resulting in limited student participation, passive learning behavior, and weak collaborative interaction during the instructional process. This study investigates the implementation of a Jigsaw-based Active Learning strategy to enhance students’ learning activeness in Islamic Religious Education at class VII.G of SMP Negeri 18 Kota Jambi, Indonesia. Employing a Classroom Action Research design, the study was conducted through two reflective action cycles involving 32 students. Data were collected through classroom observations, semi-structured interviews, reflective field notes, and learning documentation, and were analyzed using descriptive quantitative analysis supported by qualitative reflective interpretation. The findings demonstrate that the Jigsaw-based Active Learning strategy substantially transformed classroom interaction patterns from passive teacher-dominated instruction into collaborative and student-centered learning engagement. Quantitatively, students’ learning activeness increased progressively from a pre-cycle average score of 61.25 with only 18.75% of students categorized as active and very active, to 65.14 in Cycle I with 37.50% learning mastery, and finally reaching 80.42 in Cycle II with 81.25% active participation. Beyond behavioral participation, the strategy also strengthened students’ communication confidence, collaborative responsibility, reflective interaction, and socio-academic engagement during the learning process. The study theoretically reinforces socio-constructivist and cooperative learning perspectives by demonstrating that meaningful engagement in faith-based education emerges through peer-mediated dialogue, collaborative knowledge construction, and reflective social interaction. Furthermore, this research proposes that Jigsaw-based Active Learning functions not merely as a cooperative instructional technique, but as a transformative socio-pedagogical framework capable of integrating cognitive understanding, ethical reflection, and participatory learning within contemporary Islamic Religious Education.